2022
DOI: 10.1021/acs.est.2c07828
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol S Impairs Behaviors through Disturbing Endoplasmic Reticulum Function and Reducing Lipid Levels in the Brain of Zebrafish

Abstract: The number of neurotoxic pollutants is increasing, but their mechanism of action is unclear. Here, zebrafish were exposed to 0, 1, 10, and 100 μg/L bisphenol S (BPS) for different durations beginning at 2 h postfertilization (hpf) to explore the neurotoxic mechanisms of BPS. Zebrafish larvae exposed to BPS displayed abnormal neurobehaviors. At 48 and 120 hpf, BPS inhibited yolk lipid consumption and reduced the lipid distribution in the zebrafish brain. Moreover, BPS downregulated the mRNA levels of genes invo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…This analysis was consistent with the results of the embryos with enlarged yolk sacs in the BPS developmental exposure experiment. This phenomenon is also reflected in other instances where BPS was demonstrated to interfere with yolk lipid consumption in zebrafish embryos [ 65 ]. This result indicates that BPS exposure may cause harmful effects on energy metabolism.…”
Section: Discussionmentioning
confidence: 59%
“…This analysis was consistent with the results of the embryos with enlarged yolk sacs in the BPS developmental exposure experiment. This phenomenon is also reflected in other instances where BPS was demonstrated to interfere with yolk lipid consumption in zebrafish embryos [ 65 ]. This result indicates that BPS exposure may cause harmful effects on energy metabolism.…”
Section: Discussionmentioning
confidence: 59%
“…The Z -stack merged fluorescence of TH-1 and DTH-1 in different layers of the brain was observed, suggesting their good diffusion in the zebrafish brain. And we found that DTH-1 had a tendency to move toward the edge of brain near the yolk, which may be due to the high lipid content in this area . Because the clogP and logD 7.4 value of the DTH-1 are about 1.6 times those of TH-1 , DTH-1 has stronger lipid solubility (Figure and Figure S2B,C).…”
Section: Resultsmentioning
confidence: 81%
“…And we found that DTH-1 had a tendency to move toward the edge of brain near the yolk, which may be due to the high lipid content in this area. 57 Because the clogP and logD 7.4 value of the DTH-1 are about 1.6 times those of TH-1, DTH-1 has stronger lipid solubility (Figure 1 and Figure S2B,C).…”
Section: ■ Introductionmentioning
confidence: 99%
“…TBPH exhibited a tendency to persist more in the brain and muscle, with longer half-lives in both female and male zebrafish. Several factors may contribute to the slower clearance rate of TBPH in brain tissue: (1) their high affinity for lipid tissues leads to accumulation in lipid-rich brain tissue over time, hindering clearance; (2) microcirculatory properties, such as slower cerebral blood flow and less dense blood vessels, contribute to prolonged retention of exposures; and (3) the presence of the blood–brain barrier presents a challenge for molecules to cross into or out of brain tissue, resulting in slower clearance rates …”
Section: Resultsmentioning
confidence: 99%